(3eMGSHI GdJcGdja GdRQGYjI (B/s - (3GMeO, LdGds; (3fXej GHQGgje, GjgGH s ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2010)
(3GdGbJUGO GdRQGYj , GdRQGYI h GbJUGOjGJgG , eMGSHI GdJcGdja aj GdefTBJ GdRQGYjI , MSGHGJ GdGfTWI GdRQGYjI , MSGHGJ GdGfJGL GdMjhGfj (B.s
(3eQGLY U(B.223s
Keywords: (3GdRQGYIs; (3GdeMGSHIs; (3eMGSHI GdJcGdjas